Mecanismos de resistência de camundongos BALB/c e C57BL/6 à infecção por Leishmania (Viannia) guyanensis - Barbara Pinheiro Mendes (2011)
The many types of clinical manifestations of leishmaniasis, resistance or susceptibility to infection is determined by factors such as parasite species and the type of immune response of the host. In this present work, BALB/c and C57BL/6 mice strains were used as experimental models of resistance to infection caused by Leishmania guyanensis, a parasite species that causes cutaneous leishmaniasis in humans and is very important in some countries of South America. The aim of this study was to investigate the mechanisms of resistance to infection caused by this species of Leishmania in these mice strains. Thus, mice of both strains were infected at the hind footpad with L. guyanensis and the course of infection was followed. Our data shows that this parasite species causes no lesion in both mice strains and that the parasites are eliminated both on the site of infection and its draining lymph node. It was also demonstrated that non-activated peritoneal macrophages of both mice strains eliminate the intracellular amastigotes in vitro. It was already known that this elimination occurs through the respiratory burst. Here we also demonstrated that L. guyanensis promastigotes induces this reaction in BALB/c macrophages in vitro, but in a lower extent in C57BL/6 macrophages. Furthermore, it was showed in this work that peritoneal macrophages of both mice strains do not produce nitric oxide when infected in vitro with L. guyanensis. The course of infection in C57BL/6 mice gp91phox (the catalytic subunit of NADPH oxidase enzyme) knockout was similar to that of the wild type mice, not presenting lesion or swelling in the footpad. However, BALB/c mice treated with apocynin, a specific NADPH oxidase inhibitor, became susceptible to infection with L. guyanensis. Our data indicates that superoxide anion and hydrogen peroxide, two respiratory burst products, are important in the elimination of intracellular amastigotes by BALB/c macrophages, in vitro. BALB/c mice apparently mount a Th1 type response to the infection with L. guyanensis, with low production of IFN-× and no production of IL-4. These results indicate that the innate immunity, through the respiratory burst, could be, at least in part, responsible for the control of infection with L. guyanensis in BALB/c mice, but not in C57BL/6 mice.